2011
DOI: 10.1007/s10750-011-0645-0
|View full text |Cite
|
Sign up to set email alerts
|

High predation is of key importance for dominance of small-bodied zooplankton in warm shallow lakes: evidence from lakes, fish exclosures and surface sediments

Abstract: The mean body size of limnetic cladocerans decreases from cold temperate to tropical regions, in both the northern and the southern hemisphere. This size shift has been attributed to both direct (e.g. physiological) or indirect (especially increased predation) impacts. To provide further information on the role of predation, we compiled results from several studies of subtropical Uruguayan lakes using three different approaches: (i) field observations from two lakes with contrasting fish abundance, Lakes River… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
92
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(105 citation statements)
references
References 54 publications
11
92
1
1
Order By: Relevance
“…Corroborating the above, our results show higher consumption of large cladocerans such as M. macrocopa and M. triserialis, regardless of water quality. It has been well documented that the overall size structure of zooplankton is smaller in lakes dominated by fish populations (Iglesias et al, 2011). The same is true for lake Xochimilco where small zooplankton dominate in terms of numbers and biomass (EnriquezGarcía et al, 2009).…”
Section: Heterocypris Incongruensmentioning
confidence: 91%
“…Corroborating the above, our results show higher consumption of large cladocerans such as M. macrocopa and M. triserialis, regardless of water quality. It has been well documented that the overall size structure of zooplankton is smaller in lakes dominated by fish populations (Iglesias et al, 2011). The same is true for lake Xochimilco where small zooplankton dominate in terms of numbers and biomass (EnriquezGarcía et al, 2009).…”
Section: Heterocypris Incongruensmentioning
confidence: 91%
“…Strengthened interspecific competition between dominants and subordinates influences the fate of the latter group, as weak competition permits an inferior species to persist for a longer period (Lie, 1973). Selective herbivory, predation, or parasitism generally suppresses the competitive capability of dominant species, allowing the coexistence of subordinate species and causing an increase in community diversity (Daleo, Alberti, Pascual, Canepuccia, & Iribarne, 2014; Hudson & Greenman, 1998; Iglesias et al., 2011; Ingram & Kirkpatrick, 2013; Kellogg & Bridgham, 2004; Lotze, Worm, & Sommer, 2000; Olff & Ritchie, 1998; Pierce, Luzzaro, Caccianiga, Ceriani, & Cerabolini, 2007; Roth, Whitford, & Steinberger, 2007; Santamaria, 2002; Smith et al., 2009). In contrast, nonselective herbivory, such as seed predation, may favor the dominant species and thus decrease overall diversity (Montgomery, 1980; Yu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Havens et al (2015), comparing 122 lakes located from 6° to 74°N and from 19° to 21°S, showed a relationship between size (as weight) of cladocerans and cyclopoid copepods and temperature. In contrast, Iglesias et al (2011) suggested that predation by fish is the major factor explaining the smaller size of zooplankton in warm lakes. Hart and Bychek (2011), in their extensive review of the many factors that could potentially influence zooplankton size, addressed extrinsic factors such as temperature, food and predation, amongst others, besides intrinsic ones.…”
mentioning
confidence: 98%